Granting specificity for breast cancer cells using a hepatitis B core particle with a HER2-targeted affibody molecule - Nishimura, Yuya; Mimura, Wakiko; Mohamed Suffian, Izzat Fahimuddin; Amino, Tomokazu; Ishii, Jun; Ogino, Chiaki; Kondo, Akihiko (Oxford University Press, 2011)
Capsid-like particles consisting of a hepatitis B core (HBc) protein have been studied for their potential as carriers for drug delivery systems (DDS). The hollow HBc particle, which is formed by the self-assembly of core proteins comprising 183 aa residues, has the ability to bind to various cells non-specifically via the action of an arginine-rich domain. In this study, we developed an engineered HBc particle that specifically recognises and targets human epidermal growth factor receptor-related 2 (HER2)-expressing breast cancer cells. To despoil the non-specific binding property of an HBc particle, we genetically deleted the C-terminal 150–183 aa part of the core protein that encodes the arginine-rich domain (ΔHBc). Then, we genetically inserted a ZHER2 affibody molecule into the 78–81 aa position of the core protein to confer the ability of target-cell-specific recognition. The constructed ZHER2-displaying HBc (ZHER2-ΔHBc) particle specifically recognised HER2-expressing SKBR3 and MCF-7 breast cancer cells. In addition, the ZHER2-ΔHBc particle exhibited different binding amounts in accordance with the HER2 expression levels of cancer cells. These results show that the display of other types of Affibody molecules on HBc particles would be an expandable strategy for targeting several kinds of cancer cells that would help enable a pinpoint DDS.